2009
DOI: 10.1002/rcm.3958
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive inter‐laboratory calibration of reference materials for δ18O versus VSMOW using various on‐line high‐temperature conversion techniques

Abstract: Internationally distributed organic and inorganic oxygen isotopic reference materials have been calibrated by six laboratories carrying out more than 5300 measurements using a variety of high-temperature conversion techniques (HTC)a in an evaluation sponsored by the International Union of Pure and Applied Chemistry (IUPAC). To aid in the calibration of these reference materials, which span more than 125 per thousand, an artificially enriched reference water (delta(18)O of +78.91 per thousand) and two barium su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
238
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 175 publications
(247 citation statements)
references
References 62 publications
(120 reference statements)
8
238
0
1
Order By: Relevance
“…MS-specific sources include ionization differences in ion sources and individual electronic amplifier characteristics resulting in incompatible slopes of isotopic scales among mass spectrometers [10,147]. Sources outside the MS include, for example, conversion effects when using water reduction in high-temperature reactions [148]. Coplen et al [149] reported that isotopic analyses in different laboratories often differ by ten times the reported total uncertainty of their measurements.…”
Section: Part 7: the Need For Contaminant-specific Isotope Reference mentioning
confidence: 98%
“…MS-specific sources include ionization differences in ion sources and individual electronic amplifier characteristics resulting in incompatible slopes of isotopic scales among mass spectrometers [10,147]. Sources outside the MS include, for example, conversion effects when using water reduction in high-temperature reactions [148]. Coplen et al [149] reported that isotopic analyses in different laboratories often differ by ten times the reported total uncertainty of their measurements.…”
Section: Part 7: the Need For Contaminant-specific Isotope Reference mentioning
confidence: 98%
“…2.1.1, an alternative method to mass spectrometry is the direct determination of oxygen isotope ratios by laser absorption spectroscopy (Brand et al 2009a, b and others).…”
Section: Watermentioning
confidence: 99%
“…This was repeated for all the produced acids. The distillates were then placed into autosampler vials and analysed using either the TCEA setup [50] or the laser absorption Cavity Ring-Down Spectrometer system (Picarro, Sunnyvale, Ca, USA) [53] in our laboratory. The results are given in Table 1.…”
mentioning
confidence: 99%
“…Water 1 is Jena tap water; waters II to IV were made by slowly distilling local tap water until the isotopic composition was reached. The oxygen isotopic composition of water (columns 2 & 6) was determined with a CRDS system; [53] the oxygen isotopic composition of the phosphoric acid (column 4) was determined using a high-temperature HTC system coupled to a Thermo Fisher Delta þ XL isotope ratio mass spectrometer [50] $ þ22 calc. * * Due to its high hygroscopicity P 4 O 10 could not be analysed reliably using the HTC system.…”
mentioning
confidence: 99%